PENGGUNAAN MEDIA DAKON BILANGAN TERHADAP HASIL BELAJAR FPB DAN KPK SISWA SDN 34 PONTIANAK - Aspriliana, Rizka; K.Y. Margiati, K.Y. Margiati; Sugiyono, Sugiyono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem in this research is "Is there any influence of media use dakon number to learning result of FPB and KPK of fourth grade student of State Elementary School 34 Pontianak Kota?". The research method used in this research is the experimental method with quasi experimental design (Quasi Experimental Design), with the Nonequivalent Control Group Design experiment design. The sample selection was done by simple random sampling technique. Data collection tool in the form of observation sheet, document of learning result, and test result of student learning in the form of essay matter with 10 question. Based on the statistical calculation of the average learning result of the final test of the experimental class 79,20 and the mean of final test result of control class 67,68 obtained the final test data counted 2,549 and ttable (Î±= 5% and dk 32 + 33 -2 = 64) of 1.670133, because tcount (2.549)> ttable (1.670133), then Ha is accepted. So, it can be concluded that there is influence of media use dakon number to learning outcomes of FPB and KPK grade IV students of State Elementary School 34 Pontianak City. From the calculation of effect size (ES), obtained ES of 0.583 (medium criterion). This means the use of media dakon number on learning FPB and KPK gives a moderate effect on student learning outcomes in grade IV State Elementary School 34 Pontianak City.Â Keywords: Influence, Media Dakon Numbers, Learning Outcomes.Â Â